Bazham tarikhnivisi bahshivahi-yi Mujahidin : (Danishjuyani Irani dar Faransah (Havadari Sabiqi Sazmani Paykar), 1985)
Once again historiography in the style of Mujahidin; a short response to the Mujahid's reaction.